1972. Safety and Immunogenicity of 15-Valent Pneumococcal Conjugate Vaccine (PCV-15) Compared with PCV-13 in Healthy Older Adults Previously Vaccinated With 23-Valent Pneumococcal Polysaccharide Vaccine (PPV23). (26th November 2018) - Buchwald, Ulrike; Peterson, James; Stacey, Helen; Julien, Katie; Sterling, Tina; Bruch, Melanie; Tamms, Gretchen; Li, Jianing; Pedley, Alison; Nolan, Katrina; Benner, Patrice; Abeygunawardana, Chitrananda; et al.
Abstract: Background: Safety and immunogenicity of a new formulation of PCV-15 (1, 3, 4, 5, 6A, 6B, 7F, 9V, 14, 18C, 19F, 19A, 22F*, 23F, 33F*) was evaluated in adults ≥65 years of age previously vaccinated with PPV23. Methods: Study subjects who received PPV23 at least 1 year prior to study entry received a single dose of either PCV-15 or PCV-13 (125/arm) and were followed for safety for 14 days postvaccination. Serotype-specific Immunoglobulin G (IgG) geometric mean concentrations (GMCs) and opsonophagocytic activity (OPA) geometric mean titers (GMTs) were measured immediately prior and 30 days postvaccination. NCT02573081 Results: Safety profiles were comparable between PCV-15 and PCV-13 recipients. Following vaccination, serotype- specific antibody responses for the 13 shared serotypes were generally comparable between recipients of PCV- 15 and PCV-13 for IgG GMCs and geometric mean fold rises (GMFRs), OPA GMTs and GMFRs, and percentages of subjects with ≥4-fold-rise from baseline. Recipients of PCV-15 had numerically higher IgG GMCs and OPA GMTs than PCV-13 recipients for two serotypes unique to PCV-15 (22F, 33F). Conclusion: PCV-15 was generally well tolerated when given as a single dose to adults ≥65 years of age previously vaccinated with PPV23. Following vaccination, serotype-specific IgG GMCs and OPA GMTs were comparable between recipients of PCV-15 and PCV-13 for 13 shared serotypes. *Not shared serotypes with PCV-13 Disclosures: U. Buchwald, Merck: Employee and Shareholder, Salary and stock options. J. Peterson, Merck: Investigator, Research grant. H. Stacey, Merckl: Investigator, Research grant. K. Julien, Merck: Investigator, Research grant. T. Sterling, Merck: Employee and Shareholder, Salary and stock options. M. Bruch, Merck: Employee and Shareholder, Salary and stock options. G. Tamms, Merck: Employee and Shareholder, Salary and stock options. J. Li, Merck: Employee and Shareholder, Salary and stock options. A. Pedley, Merck: Employee and Shareholder, Salary and stock options. K. Nolan, Merck: Employee and Shareholder, Salary and stock options. P. Benner, Merck: Employee and Shareholder, Salary and stock options. C. Abeygunawardana, Merck: Employee and Shareholder, Salary and stock options. M. Winters, Merck: Employee and Shareholder, Salary and stock options. M. Kosinski, Merck: Employee and Shareholder, Salary and stock options. J. Stek, Merck: Employee and Shareholder, Salary and stock options. L. Musey, Merck: Employee and Shareholder, Salary and stock options.